2012
DOI: 10.1155/2012/728417
|View full text |Cite
|
Sign up to set email alerts
|

Serum IL-18 Is Closely Associated with Renal Tubulointerstitial Injury and Predicts Renal Prognosis in IgA Nephropathy

Abstract: Background. IgA nephropathy (IgAN) was thought to be benign but recently found it slowly progresses and leads to ESRD eventually. The aim of this research is to investigate the value of serum IL-18 level, a sensitive biomarker for proximal tubule injury, for assessing the histopathological severity and disease progression in IgAN. Methods. Serum IL-18 levels in 76 IgAN patients and 36 healthy blood donors were measured by ELISA. We evaluated percentage of global and segmental sclerosis (GSS) and extent of tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…In addition, in both patients [39][41] and animal models [42], [43], IL-1β plays a pathogenic role in the evolution of IgAN, while patients with IgAN have been shown to have increased IL-18 levels in urine [44] and serum [45] and this is considered as a prognostic factor in these patients [45]. Mature IL-1β and IL-18 are generated from their respective precursors, pro-IL-1β and pro-IL-18, by active caspase-1 produced by the NLRP3 inflammasome [32], [46].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in both patients [39][41] and animal models [42], [43], IL-1β plays a pathogenic role in the evolution of IgAN, while patients with IgAN have been shown to have increased IL-18 levels in urine [44] and serum [45] and this is considered as a prognostic factor in these patients [45]. Mature IL-1β and IL-18 are generated from their respective precursors, pro-IL-1β and pro-IL-18, by active caspase-1 produced by the NLRP3 inflammasome [32], [46].…”
Section: Discussionmentioning
confidence: 99%
“…Levels of advanced oxidative protein products in 292 patients with IgA nephropathy from the USA and Italy correlated with the rate of decline in renal function (r = −0.33, p = 0.008) measured by eGFR [32]. An increased serum level of interleukin-18, a cytokine associated with renal injury in ischemia-reperfusion models, was significantly correlated with the rate of loss of renal function (r = 0.242, p = 0.021), also measured by eGFR, in a cohort of 76 Chinese patients with IgA nephropathy with moderate to severe histologic changes on kidney biopsy (greater than 25% of glomeruli with crescents, segmental sclerosis, or global sclerosis) [93]. …”
Section: Biomarkers Of Iga Nephropathymentioning
confidence: 99%
“…A clinical study in Finland enrolled total of 174 patients with IgAN found that there was a marked increase in inflammatory markers such s‐albumin, high‐sensitivity C‐reactive protein, and white blood cells, which were suggested to be associated with the progression of IgAN 7. Moreover, increasing clinical evidences further demonstrated that the production of proinflammatory cytokines such IL‐18 and IL‐1β were dramatically upregulated in IgAN patients and this is considered as a prognostic factor in these patients 8, 9, 10. It has been documented that mature IL‐18 and IL‐1β are generated via the activation of Nlrp3 inflammasome 13, 27.…”
Section: Discussionmentioning
confidence: 99%